2011
DOI: 10.1007/s11214-011-9826-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent Results from Titan’s Ionosphere

Abstract: Titan has the most significant atmosphere of any moon in the solar system, with a pressure at the surface larger than the Earth's. It also has a significant ionosphere, which is usually immersed in Saturn's magnetosphere. Occasionally it exits into Saturn's magnetosheath. In this paper we review several recent advances in our understanding of Titan's ionosphere, and present some comparisons with the other unmagnetized objects Mars and Venus. We present aspects of the ionospheric structure, chemistry, electrody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…[49] We note again that photoelectrons observed in the tail are sensitive tracers of a magnetic connection to the dayside ionosphere, and are consistent with the observed field direction [Wei et al, 2011] for all the encounters reported here (T9, T75, T63) [cf. Coates et al, 2007Coates et al, , 2011aCoates et al, , 2011bWellbrock et al, 2012]. Additional observations during other tail photoelectron intervals at Titan encounters T40, T17, T15 are reported by Wellbrock et al, 2012. [50] Acknowledgments.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[49] We note again that photoelectrons observed in the tail are sensitive tracers of a magnetic connection to the dayside ionosphere, and are consistent with the observed field direction [Wei et al, 2011] for all the encounters reported here (T9, T75, T63) [cf. Coates et al, 2007Coates et al, , 2011aCoates et al, , 2011bWellbrock et al, 2012]. Additional observations during other tail photoelectron intervals at Titan encounters T40, T17, T15 are reported by Wellbrock et al, 2012. [50] Acknowledgments.…”
Section: Discussionmentioning
confidence: 74%
“…[2] Cassini has revealed many important aspects of Titan's ionosphere (e.g., reviews by Cravens et al [2009] and Coates et al [2011a]). Titan, orbiting at 20 Saturn radii (R s ) from Saturn, spends most of its time in Saturn's magnetosphere, and recent papers have documented the variety of upstream conditions at Titan's orbit [Rymer et al, 2009Arridge et al, 2011a.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Wellbrock et al (2009), A. Wellbrock (2021, in preparation) and Coates et al (2009Coates et al ( , 2011 show that heavy anion densities under illuminated conditions past the terminator are lower than unilluminated conditions in the deeper nightside ionosphere, as observed during flybys such as T57. The higher densities of heavy anions in unilluminated conditions could provide a competing pathway to heavy cation production.…”
Section: Variations Between Flybysmentioning
confidence: 97%
“…Wellbrock 2021, in preparation). On the other hand, Wellbrock et al (2009), A. Wellbrock (2021, in preparation) and Coates et al (2009Coates et al ( , 2011 show that heavy anion densities under illuminated conditions past the terminator are lower than unilluminated conditions in the deeper nightside ionosphere, as observed during flybys such as T57. The higher densities of heavy anions in unilluminated conditions could provide a competing pathway to heavy cation production.…”
Section: Variations Between Flybysmentioning
confidence: 97%
“…Due to Titan's extended atmosphere the effects of solar EUV radiation on ions are seen past the terminator, up to SZA values of 135°at 1000 km (Ågren et al 2009;Coates et al 2009Coates et al , 2011Wellbrock et al 2009Wellbrock et al , 2013A. Wellbrock 2021, in preparation), although at high SZA values the solar radiation is attenuated by passing through more of Titan's atmosphere studied the diurnal variations of positive ions, finding that light ions were strongly depleted on the nightside while the heavy ions were moderately depleted and the most significant diurnal variations were seen at low altitudes.…”
Section: Variations Between Flybysmentioning
confidence: 99%